Develop Prototype of Web-Based Computer Problem Information System - Shobana, Subramaniam (2003)
The aim of this project is to develop a prototype of Web based Computer Problem Information System. This system is an assistant tool for user to find information regarding computer problem especially in finding solution. It applies knowledge base and web base application in order to add element such as user friendly, usefulness, pleasing and informative. This prototype has been developed using Object-oriented approach focusing on Object Modeling Technique methodology and Rapid Application Development with Unified Modeling Language notation. The development of this prototype starts with analysis phase and ended with testing. This project discusses some findings, problem encountered and limitation of the project’s development. Finally, brief recommendation given as contribution to the future development.